Integrative Medicine for Pain Management in Oncology: Society for Integrative Oncology–ASCO Guideline. Issue 34 (1st December 2022) - Mao, Jun J.; Ismaila, Nofisat; Bao, Ting; Barton, Debra; Ben-Arye, Eran; Garland, Eric L.; Greenlee, Heather; Leblanc, Thomas; Lee, Richard T.; Lopez, Ana Maria; Loprinzi, Charles; Lyman, Gary H.; et al.
Abstract : PURPOSE: The aim of this joint guideline is to provide evidence-based recommendations to practicing physicians and other health care providers on integrative approaches to managing pain in patients with cancer. METHODS: The Society for Integrative Oncology and ASCO convened an expert panel of integrative oncology, medical oncology, radiation oncology, surgical oncology, palliative oncology, social sciences, mind-body medicine, nursing, and patient advocacy representatives. The literature search included systematic reviews, meta-analyses, and randomized controlled trials published from 1990 through 2021. Outcomes of interest included pain intensity, symptom relief, and adverse events. Expert panel members used this evidence and informal consensus to develop evidence-based guideline recommendations. RESULTS: The literature search identified 227 relevant studies to inform the evidence base for this guideline. RECOMMENDATIONS: Among adult patients, acupuncture should be recommended for aromatase inhibitor–related joint pain. Acupuncture or reflexology or acupressure may be recommended for general cancer pain or musculoskeletal pain. Hypnosis may be recommended to patients who experience procedural pain. Massage may be recommended to patients experiencing pain during palliative or hospice care. These recommendations are based on an intermediate level of evidence, benefit outweighing risk, and with moderate strength of recommendation. The quality of evidence for other mind-body interventions or natural products for pain is either low or inconclusive. There is insufficient or inconclusive evidence to make recommendations for pediatric patients. More research is needed to better characterize the role of integrative medicine interventions in the care of patients with cancer. Additional information is available at https://integrativeonc.org/practice-guidelines/guidelines and www.asco.org/survivorship-guidelines .